Wastewater collection system failures in a capital city: analysis and sustainable prevention - Andres Marquez (IWA Publishing, 2021)
An analysis of failures in a capital city's wastewater collection system was carried out and recommendations were made for sustainable preventive measures based on a risk of failure assessment. Most failures in sewer lines were associated with blockage caused by sediment accumulation and clogging from fats, oils and/or grease dumped by restaurants along several streets, combined with poor or nonexistent maintenance of the lines. Sewer lines in streets with higher risk levels due to multiple food establishments along those streets experienced most of the failures. Sustainability of the proposed maintenance was evidenced since it reduces costs and exposure to harmful substances and hazardous conditions as well as minimizing environmental impacts. HIGHLIGHTS Wastewater collection system failures.; Sustainable preventive measures.; Sediment accumulation and clogging from dumped fats, oils and/or grease.; Sewer lines in streets with higher risk levels due to multiple food establishments along those streets experienced most of the failures.; Sustainability: reduces costs, exposure to harmful substances and hazardous conditions, and minimizes environmental impacts.;